Focus A Forum on Teaching and Learning in Utah Community Colleges / Don A. Carpenter, Ed. - Carpenter, Don A. (Distributed by ERIC Clearinghouse, 1993)
This volume of an annual publication concerning issues relevant to Utah's two-year colleges provides the following articles by community college faculty on instructional issues and methods: (1) "Teaching Real-World Math Concepts in an Introductory Algebra Telecourse," by Loretta Palmer; (2) "Collaborative Learning in the Community College Classroom," by Steffeny Fazzio; (3) "The Case for Case Studies," by Gary T. Ward (an exploration of the merits and drawbacks of case analysis, with a description of its techniques and validation); (4) "Understanding the 'Irrational Student,'" by Michael Kowalski (suggesting that rational thought is relative and that teachers must strive to understand "irrational" students); (5) "Cross Cultural and International Curricula Enhancement: Meeting the Needs of Utah Students," by Ron Hammond; (6) "Teaching the Intangibles," by Karen Templeton (offering suggestions for nursing educators on encouraging students' curiosity, helping them trust their own interpretations of the findings of health assessments, and teaching them to practice empathy, to experiment, and to be colleagues in learning); (7) "From Quiet Writing to Multimedia: Innovations in English," by Lee Ann Mortensen and Chloe M. Nichols (a discussion of computer-assisted methods of teaching writing); and (8) "Leadership and Third-Order Change," by Pamela Gardner (an analysis of changes in the modern world based on the contradictions established in chaos theory). (MAB)
ERIC Document Number: ED363377.
Availability: Utah System of Higher Education, 3 Triad Center, Suite 550, Salt Lake City, UT 84180-1205.
Keywords: Community Colleges.; Computer Oriented Programs.; Computer Uses in Education.; Cooperation.; Individual Psychology.; Instructional Materials.; Mathematics Instruction.; Program Descriptions.; Teacher Expectations of Students.; Teacher Influence.; Teacher Student Relationship.; Two Year College Students.; Two Year Colleges.; Writing Instruction.